Be aware of the effects of glucocorticoids on SIADH: A case report. Issue 7 (February 2019) - Li, Huaqian; Huang, Lijun; Wu, Ge; Chen, Xianmei; Zheng, Qiaoan; Su, Faming; Liang, Maoshan; Chen, Xiaoming
Abstract: Rationale: Hyponatremia is one of the most common electrolyte disorders in clinic. Due to the complicated etiology and the nonspecific clinical manifestations, the diagnosis of hyponatremia is a complicated process. A variety of clinical disorders can cause inappropriately increased antidiuretic hormone (ADH) secretion, leading to inappropriate water retention and consequent hyponatremia. The most common cause of hyponatremia in hospital inpatients is syndrome of inappropriate antidiuretic (SIADH). The action of glucocorticoid against pituitary posterior lobe can reduce the secretion of ADH. However, the effect of hormone on diuretic hormone during treatment has been less reported. Patient concerns and diagnosis: The patient in this case report was misdiagnosed as anterior pituitary hypofunction because of the long-term glucocorticoid therapy was effective in this patient, and the patient was finally diagnosed as SIADH after reassessment. The patient is a 76-year-old male with long-term symptomatic hyponatremia after traumatic brain injury (TBI). The patient has been consistently diagnosed as anterior pituitary hypofunction. Based on the diagnosis, glucocorticoid replacement therapy was administered. The serum sodium of the patient gradually increased to normal level after hydrocortisone intravenous injection but dropped again after switch to hydrocortisone oral administration. Through examination and analysis of the patient status during the five-time hospitalization, syndrome of inappropriate antidiuretic hormone (SIADH) was considered. Interventions: Water intake limitation and oral furosemide and antisterone were administered after glucocorticoid therapy was stopped. Outcome: The serum sodium level of the patient gradually increased and maintained within normal range based on his clinical follow-up. Lessons: For hyponatremia with effective glucocorticoid treatment, SIADH should still be excluded.